Implementation Of Gaze Stability Exercise With Ergonomic Approach Based On Home Training Program in Improving Balance in The Elderly - Putri, Fadma; Fidyatul Nazhira; Swandari, Atik; Larasati, Nabila (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: The aging process is characterized by a decrease in physiological function, which has an impact on balance disorders and can increase the risk of falling in the elderly. This study was to analyze differences in the balance of the elderly before and after the implementation of gaze stability exercise with an ergonomic approach based on a home exercise program. Methods: This research is an experimental study with a pre and post test one group design. Participants underwent training every day for 6 weeks. Balance ability was measured using time up and go test pre and post intervention. Results: There was a significant difference in the pre and post intervention time up and go test scores with p < 0.05. Conclusion: based on the results of the study, the implementation of gaze stability exercise with an ergonomic approach based on a home exercise program was significant in improving the balance of the elderly by 18.6% compared to before receiving the exercise.